2017
DOI: 10.1108/jeim-01-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Does e-readiness of citizens ensure better adoption of government’s digital initiatives? A case based study

Abstract: Purpose The purpose of this paper is to critically examine and evaluate the “E-Readiness” of the citizens of India which is imperative to make such large scale e-government initiatives a success. The researchers tried to compare India with some developed and developing countries where the e-government model have been implemented successfully, looking at the prime factors for the successful implementation. Design/methodology/approach The methodology adopted for this study is exploratory in nature. A comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Researchers have indicated that an innovation model guided by user demand and participation can promote sustainable enterprise development (Bock et al , 2016; Schweisfurth, 2017). In particular, in some emerging economies, scholars have discovered that innovation involving users can promote innovative practices by enterprises and even the government (Ghosh Roy and Upadhyay, 2017; Upadhyay and Jahanyan, 2016).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Researchers have indicated that an innovation model guided by user demand and participation can promote sustainable enterprise development (Bock et al , 2016; Schweisfurth, 2017). In particular, in some emerging economies, scholars have discovered that innovation involving users can promote innovative practices by enterprises and even the government (Ghosh Roy and Upadhyay, 2017; Upadhyay and Jahanyan, 2016).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…E-readiness is a ‘measure that shows the ability of an entity to leverage the ICT’ and is considered to be the basic imperative for any e-government initiative to be a success (Ghosh Roy & Upadhyay, 2017). The entity here could be the government, or any agency, an individual, or even society (Omari & Al-Hussein, 2006).…”
Section: Review Of Literaturementioning
confidence: 99%
“…According to a Gartner Group report, Indian governments (at centre, states and local levels) spent nearly $7.2 billion in 2016 on the development and maintenance of e-governance (Chandran, 2016), and this figure was estimated at around $8 billion for the year 2018. E-government investments in India had seen a ‘ten- fold increase’ in 2015 with the launch of the Digital India Mission as compared to the previous three years (Ghosh Roy & Upadhyay, 2017). Despite these significant investments, according to the 2018 e-government survey by the United Nations, India’s E-government Development Index (EGDI) was 0.5669, just above the world average of 0.55.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon also requires each country to adapt to become an underdeveloped party (Ahmed, As-Saber, Fry, & Smith, 2018). The presence of technological and information developments has changed the way the interaction between government and society (Brooks, 2016;Ghosh Roy & Upadhyay, 2017). According to (Alghamdi, Goodwin, & Rampersad, 2016) that the use of information and communication technology influences public sector organizations to shift the culture and activities of organizations that were formerly manual or traditional and then turned into technology-based organizational activities (Alghamdi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research related to e-readiness has been carried out at the state level, private organizations, communities and employees (Ghosh Roy & Upadhyay, 2017;Kasravi, Ahmadinia, & Rezaiee, 2017;Sigwejo & Pather, 2016). Dukic, et.al (2016) who examined the level of egovernment readiness of government employees in Croatia, which focused on ICT literacy competencies and standards.…”
Section: Introductionmentioning
confidence: 99%